Starševska upravičenja v zvezi s šolanjem otroka - Novak, Barbara (Pravni letopis, 2009)
In the school parental rights to educate and to bring up their children meet the state mandate of the school to educate and to bring up their pupils. The relations between parents, school and state also concern children's rights. It is unusual when the state, the school, parents and the child create their relationship fully without conflicts, but there are not many areas of social life where the conflicts between children, parents and the state are so clearly manifested as in the school system. For solution of these conflict relations it is of great importance to follow the principle of the child benefit.
Keywords: child; človekove pravice; education; human rights; izobraževanje; otroci; starši; šole; vzgoja